Geographic Variation in Knowledge of Palliative Care Among US Adults: Findings From 2018 Health Information National Trends Survey. (March 2021) - Chen, Guanming; Hong, Young-Rock; Wilkie, Diana J.; Kittleson, Sheri; Huo, Jinhai; Bian, Jiang
Background: Public knowledge and awareness of palliative care (PC) is important to its effective use. However, it remains unclear whether the geographic variation in knowledge of PC exits in the United States. This study examined the national geographic variation in knowledge of PC. Methods: The study sample was obtained from the 2018 National Cancer Institute's Health Information National Trends Survey. Basic knowledge of PC, goal concordant treatment, misconceptions, and primary information source of PC were compared across 4 census regions. Multivariable logistic regression was used to examine factors associated with awareness of PC among 9 census divisions. Results: A total of 3194 respondents (weighted sample size: 229 591 005) were included in this study. Overall, 29% of all respondents reported having knowledge of PC; 32.9% of those residing in Northeast had some knowledge of PC, followed by 30.8% in the South, 26.2% in Midwest, and 25.6% in West. By census divisions, respondents residing in 3 divisions were more likely to have PC knowledge (New England, odds ratio: 3.06, 95% CI: 1.48-6.32, P = .003; South Atlantic, odds ratio: 1.96, 95% CI: 1.15-3.35, P = .014; Pacific, odds ratio: 1.86, 95% CI: 1.12-3.09, P = .018) compared to those in the Mountain division. Conclusions: The variation of PC knowledge on census division and state level in 2018 was consistent with the real-world geographic disparities in the availability of PC programs. These findings represent an opportunity for minimizing the gap of geographic disparity by initiating strategic programs and promoting PC programs nationwide.